2018
DOI: 10.2147/ceg.s153858
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline for reverting hepatorenal syndrome: a prospective, observational, single-center study

Abstract: ObjectiveTo evaluate the effectiveness of noradrenaline for the treatment of hepatorenal syndrome (HRS).BackgroundHRS represents the development of renal failure in cirrhotic patients. The standard treatment for HRS is terlipressin, which, as opposed to noradrenaline, is more expensive and less accessible in most tertiary care centers.Patients and methodsThirty consecutive patients with HRS type 1 received noradrenaline (1–4.0 mg/hour) and albumin for 14 days. The parameters recorded were: serum creatinine lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
0
10
0
3
Order By: Relevance
“…In patients with HRS-1, noradrenaline was shown to be as effective as terlipressin in the treatment of HRS in two small controlled clinical trials 70,71 and in a recent prospective study. 82 However, in a recent randomised trial, terlipressin was shown to be more effective than noradrenaline in the treatment of HRS in patients with ACLF; 83 this is probably related to the fact that noradrenaline, unlike terlipressin, has no effect on portal pressure 84 or on the expression of inducible NOS. 85 Despite these limitations, the use of norepinephrine for the treatment of HRS is tempting because it is a cheaper than terlipressin, although it should be administered through a central venous line and under continuous monitoring, so it cannot be used outside intensive care units.…”
Section: Renal Hypoperfusionmentioning
confidence: 99%
“…In patients with HRS-1, noradrenaline was shown to be as effective as terlipressin in the treatment of HRS in two small controlled clinical trials 70,71 and in a recent prospective study. 82 However, in a recent randomised trial, terlipressin was shown to be more effective than noradrenaline in the treatment of HRS in patients with ACLF; 83 this is probably related to the fact that noradrenaline, unlike terlipressin, has no effect on portal pressure 84 or on the expression of inducible NOS. 85 Despite these limitations, the use of norepinephrine for the treatment of HRS is tempting because it is a cheaper than terlipressin, although it should be administered through a central venous line and under continuous monitoring, so it cannot be used outside intensive care units.…”
Section: Renal Hypoperfusionmentioning
confidence: 99%
“…124 Noradrenaline at a dose of 0.5-3mg/h is infused continuously dose is gradually increased to achieve a raise in arterial blood pressure and improvement in renal parameters in HRS-AKI. 125,126 In a metaanalysis that extracted data from four studies only, no difference in reversal of HRS, 30-day mortality or recurrence of HRS was seen between terlipressin and norepinephrine. [127][128][129][130] Whereas terlipressin has been associated with cardiovascular and ischemic complications, norepinephrine was shown to have lower incidence of such adverse events.…”
Section: Vasoconstrictor Agents and Albuminmentioning
confidence: 99%
“…The authors observed that treatment with terlipressin was associated with better overall and complete response than treatment with other vasopressors 1 . While midodrine and octreotide combination has been associated with inferior response in comparison to terlipressin, several randomised trials have demonstrated similar responses with noradrenaline and terlipressin 3‐6 . It would be interesting to know the details of the vasopressors that were used in this study apart from terlipressin.…”
mentioning
confidence: 90%
“…HRS cannot be diagnosed in the presence of hypotension and we would like to know the number of patients with hypotension in the study cohort. Apart from these factors, only a small number of patients received other vasopressors, which may have led to the discrepant observations in this group 1,3‐6 …”
mentioning
confidence: 90%